KESEHATAN Mendanau Island Mangrove Ecosystem Health and Canopy Cover Belitung Regency - muhammad rizqi ramadhani; Sudirman Adibrata; Artur M Farhaby (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Research on the mangrove ecosystem on Mendanau Island was carried out using the hemispherical photography method. This study aims to determine the health and canopy cover of mangrove ecosystems. The results showed that four mangrove species were found, namely Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, and Bruguiera gymnorrhiza. The substrate includes loamy sand and sandy loam which support the growth of mangroves from the Rhizophoraceae family. The percentage of canopy cover obtained on average was 84.08% of all research stations which were categorized as Good based on the Decree of the Minister of Environment No. 201 of 2004. The percentage value of canopy cover is 84.08% and the average tree density is 2,375 trees/ha indicating that the health condition of the mangrove ecosystem on Mendanau Island is still good and very dense.